[Maqueripe Bay, Trinidad, B.W.I.] - (:unkn) unknown (Unknown, 2011)
The postcard shows Maqueripe Bay which is situated at the end of the Tucker Valley Road in Chaguaramas. The beach was a popular resort in the 1930's and 1940's but access was restricted in 1944 when the Trinidad and Tobago Government leased the area to the United States military. In the postcard, changing rooms. This postcard is postmarked 20 March, 1936 and affixed is a one cent Panamanian postage stamp.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; 1936; Beaches--Trinidad and Tobago; Bays--Trinidad and Tobago; Inlets--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Maqueripe Bay